The effect of problem-solving learning models on creative thinking skills in science subjects - Emelia Debora; Heffi Alberida; Ardi Ardi; Siska Alicia Farma (Universitas Ahmad Dahlan, 2020)
The purpose of this study was to analyze the effect of applying the Problem Solving learning model to the creative thinking abilities of grade VII students at one of the SMPN in Padang in 2019/2020. This type of research is a quasi-experimental study using the Randomized Control Group Posttest Only Design. This study's population was all students of class VII at one of the SMPN in Padang in 2019/2020; there were six classes. The research sample is class VII 3 (experimental class) and class VII 5 (control class). Sampling uses a purposive sampling technique. The instrument used was an observation sheet of students' creative thinking abilities and a posttest creative thinking sheet. Based on the study results, it can be concluded that the students' creative thinking ability in the experimental class is higher than the control class with the average value of the experimental class creative thinking test (52.45) and the control class (39.39). Data analysis using t-test showed that t count (3.66)> t table (1.67). So the conclusion is the Problem Solving learning model has a positive effect on the creative thinking ability of grade VII students at one of the SMPN in Padang.